La declaratoria de adoptabilidad, frente al incumplimiento de las obligaciones parentales, en el cantón San Miguel, año 2022. - Sánchez Coca Kerly Nagiely (2025)
The work entitled: "The declaration of adoptability, facing the non-compliance of parental obligations, in the canton of San Miguel, year 2022". First of all, it covers the rights and obligations derived from the parental authority that both the father and the mother owe to their children due to the parental co-responsibility, consequently, both are equally responsible for the integral development of children and adolescents, therefore, they must provide what is necessary both affectively and materially. However, sometimes parents do not provide the necessary environment for minor children to be able to develop their capacities and, by their behavior, place the minor in a situation of risk and possible violation of their rights, which is why the research question is: How does non-compliance with parental obligations affect the declaration of adoptability in the canton of San Miguel, year 2022? In order to clarify this question, the research has had to propose several specific objectives of the work, to finally reach the general objective of the research, which is: To analyze the limit of non-compliance with parental obligations in the canton of San Miguel, year 2022: To analyze the limit of non-compliance with parental obligations to produce the declaration of adoptability, in the San Miguel canton, year 2022. With respect to the Methodological Framework, a mixed approach was implemented that incorporated both qualitative methods and the analysis of documentary data (regulations, doctrine and jurisprudence); as well as the quantitative approach that validates the survey data through the opinion of experts. For the processing of the information, the interpretative method was mainly used to analyze the information of the Constitution of the Republic of Ecuador, the Civil Code, the Code of Childhood and Adolescence, doctrine and jurisprudence. Regarding the quantitative approach, a survey was used to validate, through the opinion of experts, what was expressed in the theoretical framework of the research work. In this way, a documentary XIII analysis guide was used to interpret the qualitative data and a survey guide was used to pose questions to the experts for the subsequent processing of the results. The main findings were presented in the conclusions along with the main recommendations. Key words: parental co-responsibility, adopter, adoptee, protective measures, adoptability declaration.